Many-Valued Logics and Bivalent Modalities - Bezerra, Edson; Venturi, Giorgio (Logic and Logical Philosophy, 2022)
In this paper, we investigate the family LS0.5 of many-valued modal logics LS0.5's. We prove that the modalities of necessity and possibility of the logics LS0.5's capture well-defined bivalent concepts of logical validity and logical consistency. We also show that these modalities can be used as recovery operators.